The effects of exchange rate volatility on sectoral exports evidence from Sweden, UK, and Germany. (9th December 2014) - Serenis, Dimitris; Tsounis, Nicholas
This paper examines the effect of exchange rate volatility for a set of three European countries, Germany, Sweden and the UK, on sectoral exports for the period 1973 q1–2010 q4. In addition to the standard deviation of moving average of the logarithm of the exchange rate, a new measure capturing unexpected fluctuation of the exchange rate is examined using the autoregressive distributed lags (ARDL) modelling for co–integration. The results suggest that there exist a long–run co–integrating relationship between the exchange rate volatility and the level of exports for the sectors examined, in the UK and Germany, but it does not have an effect on the exports of Sweden.